¿Quién causa tanta alegría? The Gritería: The Safeguarding of Intangible Cultural Heritage Inside and Outside Nicaraguan Borders - Chang Vargas, Giselle (2023)
The Nicaraguan festivity dedicated to the Immaculate Conception of the Virgin Mary is a very vast topic. In this study, our purpose is an approach to the Gritería, an activity celebrated the day before. It is intended to show that the heritage value of a cultural asset is a process that is built with the creation, appropriation, resemantization and innovative adaptation to the circumstances of the environment shared by a group, which considers it as an identity reference. This is the case of the Gritería, an example of the living culture of the Nicaraguan people, of national coverage and that has migrated beyond those borders. Ethnographic work and the use of qualitative social research techniques were applied in different communities in Nicaragua; as a complement, some references are presented to the celebration in countries where Nicaraguans have emigrated. The participatory management in the organization of this important celebration is pointed out, which, wherever it is celebrated, maintains the function of cohesion of the Nicaraguan people and the meeting of its traditions. The result of the study shows that despite the differences, the Gritería is an element of patrimonial value, of meaning for different sectors of the Nicaraguan people, whether or not they believe, the Catholic Church and the Government.